The cultural and religious significance of Central Philippine University among fifty-selected 1965 to 1975 college graduates presently residing in Iloilo City. - Kabayao, Farida Pineda
This research study is about the religious and cultural significance of Central Philippine University among selected college graduates between the period 1965 to 1975, specifically those who maintain residence in Iloilo City up to the present., Various religious and cultural events and activities were realized during the chosen decade wherein CPU students gave active participation and personal involvement. These and many other `strategies' are believed to have resulted in the enrichment of the students' college life beyond the demands of academic discipline at Central Philippine University.